A atividade de trabalho de coordenadores de cursos de graduação de uma universidade pública do nordeste do Brasil - Sousa, Valéria Nicolau de (2020)
This research proposed to analyze the work activity of undergraduate coordinators, who works at a higher education public institution. The theories used were the Psychodynamics of Work and activity-centered ergonomics, which study work and its implications for mental and physical health. The specific goals were: Investigating the existence of training for the exercise of the function; Identifying the prescriptions for the function. Confronting the prescriptions with the work that is actually performed; Ascertain what are the characteristics of work conditions and organization; Identifying the sources of work's suffering and pleasure; Surveying the variability in work and their facing strategies: Examining the issue of work's recognition; Verifying the way that subjective relationships are presented; The theoretical approaches used were the Psychodynamics of work and the Ergonomics of Activity. This research is qualitative and exploratory. A semi-structured interviews was used as a method of data collection. The participants were nine coordinators, most of them are women, married, with children, and linked to four teaching areas. It was chosen as a thematic content analysis through categories. The main results showed that, in the working conditions, the psychological risks from the high demand of work stood out, in addition to the physical and ergonomic risks associated with the physical structure of the work. Pleasure and recognition at work were associated with the resolution of demands and public recognition, especially by students. Leave from work is avoided as much as possible, which denotes zeal for work, which, however, can compromise health. It is noteworthy be noted that the main motivation of a coordinator is to be able to contribute to the professional training of students. Interpersonal relationships appear as an important source of suffering. It is concluded that the psychodynamics of work and activitycentered ergonomics were useful to understand aspects of a coordinator's work that are related to mental health. Some aspects of work organization need to be reviewed for an improvement in worker activity. It is hoped that this study can be used both to support institutional actions in favor of improving health in the coordinator's work and to justify the establishment of a financial gratification proportional to the service provided by this public server to the university